2009
DOI: 10.1007/s10661-009-0938-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial activities and trace element contents in an urban soil

Abstract: Soil biological properties are influenced by trace metals. The main sources of these pollutants in the urban areas are industrial plants, power stations, domestic heating systems and motor vehicles. The aim of this work was to evaluate, in relation to distance from urban roads, soil trace metal concentrations (Pb, Cu, Cr, Cd and V) and their influence on C-microbial biomass as well as on soil respiration and enzyme activities (phosphatase glucosidase, galactosidase, xylanase, cellulase, trealase, protease and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(49 citation statements)
references
References 39 publications
3
44
0
1
Order By: Relevance
“…These authors concluded that the concentrations of metals are not the dominant factor controlling variability in SQ, and soil texture, pH and SOM must be considered to affect this variability, which has often been ignored in urban systems. Papa et al (2010) determined urban SQ evaluating the influence of soil trace metal concentrations in relation to distance from urban roads on MBC, respiration and eight enzyme activities, observing a negative relationship between microbial activity and metal concentration. Santorufo et al (2012a) assessed urban SQ by integrating chemical and ecotoxicological approaches.…”
Section: Urban Management and Soil Quality Indicatorsmentioning
confidence: 99%
“…These authors concluded that the concentrations of metals are not the dominant factor controlling variability in SQ, and soil texture, pH and SOM must be considered to affect this variability, which has often been ignored in urban systems. Papa et al (2010) determined urban SQ evaluating the influence of soil trace metal concentrations in relation to distance from urban roads on MBC, respiration and eight enzyme activities, observing a negative relationship between microbial activity and metal concentration. Santorufo et al (2012a) assessed urban SQ by integrating chemical and ecotoxicological approaches.…”
Section: Urban Management and Soil Quality Indicatorsmentioning
confidence: 99%
“…The total soil sample (about 300 kg) was transported to the laboratory and subsequently used to prepare the pot experiment with M. jalapa. The soil was characterised by physical and chemical analysis according to the Italian Official Methods of soil chemical analysis (Ministry of Agricultural, Food and Forestry Policies 1999) for its heavy metal concentration by following previously described procedures for rhizosphere and leaf analysis (Papa et al 2010;Bartoli et al 2012). The analyses were repeated three times.…”
Section: Soil Sampling and Characterisationmentioning
confidence: 99%
“…The Cd, Cr, Cu, Pb and Ni concentrations were measured via graphite furnace AAS, and the Zn concentration was measured by flame AAS. Accuracy was examined by concurrent analysis of standard reference materials by the Resource Technology Corporation (Laramie, WY, USA); the recovery ranged from 90 % to 100 % for each element (Papa et al 2010;Bartoli et al 2012). The analyses were performed three times.…”
Section: Heavy Metal Concentration Analysis In the M Jalapa Rhizosphmentioning
confidence: 99%
“…Soil microbial activity and diversity are highly sensitive to soil contamination by organic and inorganic pollutants (Papa et al 2010;Prasad et al 2012;Thavamani et al 2012;Zhang et al 2014). Bacterial functional diversity has been significantly decreased with increasing soil pollution (Stefanowicz et al 2008;Qu et al 2011).…”
Section: Introductionmentioning
confidence: 99%